Implications of Sea Ice Management for Arctic Biogeochemistry - Miller, Lisa L.M.; Fripiat, François; Moreau, Sébastien; Nomura, Daïki; Stefels, Jacqueline; Steiner, Nadja; Tedesco, Letizia; Vancoppenolle, Martin (2020)
info:eu-repo/semantics/published